Ameliorative Role of Nutraceuticals on Neurodegenerative Diseases Using the Drosophila melanogaster as a Discovery Model to Define Bioefficacy. Issue 5 (4th July 2022) - Himalian, Ranjana; Singh, Sandeep Kumar; Singh, Mahendra Pratap
Abstract: Neurodegeneration is the destruction of neurons, and once the neurons degenerate they can't revive. This is one of the most concerned health conditions among aged population, more than ∼70% of the elderly people are suffering from neurodegeneration. Among all of the neurodegenerative diseases, Alzheimer's disease (AD), Parkinson's disease (PD) and Poly-glutamine disease (Poly-Q) are the major one and affecting most of the people around the world and posing excessive burden on the society. In order to understand this disease in non-human animal models it is pertinent to examine in model organism and various animal model are being used for such diseases like rat, mice and non-vertebrate model like Drosophila. Drosophila melanogaster is one of the best animal proven by several eminent scientist and had received several Nobel prizes for uncovering mechanism of human related genes and highly efficient model for studying neurodegenerative diseases due to its great affinity with human disease-related genes. Another factor is also employed to act as therapeutic or preventive method that is nutraceuticals. Nutraceuticals are functional natural compounds with antioxidant properties and had extensively showed the neuroprotective effect in different organisms. These nutraceuticals having antioxidant properties act through scavenging free radicals or by increasing endogenous cellular antioxidant defense molecules. For the best benefit, we are trying to utilize these nutraceuticals, which will have no or negligible side effects. In this review, we are dealing with various types of such nutraceuticals which have potent value in the prevention and curing of the diseases related to neurodegeneration. Highlights: Neurodegeneration is the silently progressing disease which shows its symptoms when it is well rooted. Many chemical drugs (almost all) have only symptomatic relief with side effects. Potent mechanism of neurodegeneration and improvement effect by nutraceuticals is proposed. Based on the Indian Cuisine scientists are trying to find the medicine from the food or food components having antioxidant properties. The best model to study the neurodegenerative diseases is Drosophila melanogaster . Many nutraceuticals having antioxidant properties have been studied and attenuated various diseases are discussed.